Microscopic Method to Verify the Efficiency of Removal of Organic Pollutants from Microplastic Surfaces - Majewski, Kamil Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purification of microplastic samples is a crucial step in environmental research, aiming to remove contaminants and ensure accurate analysis. This study explores various methods for purifying microplastics, focusing on the removal of organic contaminants, specifically fulvic acids. Comparative analysis using microscopic imaging techniques was conducted to evaluate the effectiveness of these methods. The results highlight the complexities involved in microplastic purification and the challenges associated with different approaches.
Keywords: microplastics; purification methods; fulvic acids; comparative analysis; microscopic imaging; environmental research